APPLYING AN IMPLEMENTATION RESEARCH LENS TO INDONESIA’S FREE NUTRITIOUS MEAL PROGRAM - Nurmansyah, Mochamad Iqbal; Fitriani, Anna (Universitas Airlangga, 2025)
The Makan Bergizi Gratis (MBG, or free nutritious meal) program was designed by the Indonesian government to enhance community nutrition, particularly for students. Ensuring the effective implementation of programs is essential to achieving various objectives. In general, implementation research serves as a method to identify implementation determinants, formulate strategies, and assess outcomes within the specific context of the MBG program. Therefore, this research aims to investigate the potential use of implementation research methodology for improving the MBG program. Research in the area may rely on the application of frameworks, theories, and models within implementation science. The methodology covered three areas: 1) delineation of the implementation process; 2) identification of factors affecting implementation, and 3) assessment of implementation outcomes. The research can concentrate on the phases of formulating implementation strategies and converting research into practice during the identification of the implementation process. Further opportunities for inquiry include investigating the factors influencing implementation, the effectiveness-implementation hybrid design, outcomes of implementation, economic evaluation, and the phases of scaling up the strategies within the MBG program. The active role of end-users can help ensure that the results are relevant and applicable in practice, thereby increasing the possibility of adoption. Keywords: Free nutritious meals, implementation science, perspectives, school-based program